The making of Europe : an introduction to the history of European unity - Dawson, Christopher, 1889-1970 (Meridian books, M35., 1956)
When most people use the expression "The Dark Ages" they are often unclear as to what they mean. For some, the period described is unbelievably long -- from the fall of the Roman Empire to the beginning of the Renaissance. This is not only incorrect historically; it is dangerously misleading. As the author indicates, the "Dark Ages" from the sixth to the tenth centuries were critical in the formation of European unity and the expansion and definition of Western Christianity. As such, the "Dark Ages" were only relatively dark; for it was during this period that the full impact of Byzantine Christianity, the rise, and formation of Moslem culture, the conversion of the barbarians, the Carolingian renaissance, and similar epochs were felt. It was during this period that medieval Europe and Catholic Christianity received their fundamental definition.